Analisis Penerapan Sistem Informasi Akuntansi terhadap Efektivitas Pengelolaan Keuangan pada Usaha Kecil Menengah pada Kabupaten Tabanan Provinsi Bali - Libraeni, Luh Gede Bevi; Kherismawati, Ni Putu Eka (Ekuitas: Jurnal Pendidikan Ekonomi, 2024)
Accounting information systems are very important systems to use, especially in the era of technological development. To support the growth and development of MSMEs, good financial management of human resources is needed to create businesses that have financial reports with clear profit and loss flows. Financial reports will help determine business decisions for MSME players. This research aims to determine the effectiveness and efficiency of using accounting information systems for financial management of MSMEs in Tabanan Regency. The type of data used in this research is quantitative data. The research method uses random sampling, with 100 respondents. This research instrument uses a questionnaire with a Technology Acceptance Model (TAM) approach, namely a conceptual model used to measure the level of technology acceptance by users. The results of this research indicate that the implementation of an accounting information system influences the effectiveness of financial management in small and medium enterprises in Tabanan Regency, Bali Province.